Faktor-Faktor Yang Mempengaruhi Keterlibatan Petani Dalam Sistim Ijon Pada Usahatani Padi (Studi Kasus Di Desa Topore Kecamatan Papalang Kabupaten Mamuju) - Arif, Muhammad Arif; Teddu, Sulaiman T (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2022)
In the context of past development, the agricultural sector was not seen as an engine driving the economy. However, when the economic crisis hit the world more specifically Indonesia, one of the sectors that was able to exist in driving the economy was the agricultural sector. This then makes the agricultural sector very important. The people's economy then emerged on the surface, this was due to the desire to increase the standard of living and the level of welfare of the farmers. In general, increasing welfare is implemented in increasing the economic capacity and purchasing power of farmers. This research is a case study conducted in Topore Village, Papalang District, Mamuju Regency, West Sulawesi Province, this research will be conducted for two months, from March to April 2020. Rice farmers involved in the bonded bond system in Topore Village are the population in this research. The total population in this study was as many as 497 people, 10% of whom were considered representative to represent the entire population. Thus, the population of 497 was drawn randomly at 10%, the number of samples representing 50 farmers. This study aims, among others, to: (1) find out what factors influence farmer involvement in the bonded rice system in lowland rice farming, and (2) examine what factors have the most dominant influence on farmer involvement in the bonded rice system. in lowland rice farming. The results showed that guarantees, agreements, procedures, and time had a significant effect on the involvement of farmers in the bonded bond system, and guarantees were the most influencing factors for the involvement of farmers in the bonded bonds system.